2018
DOI: 10.1590/s1677-5538.ibju.2017.0520
|View full text |Cite
|
Sign up to set email alerts
|

Sexual complications of penile frature in men who have sex with men

Abstract: Objectives:Evaluate the demographic data, etiology, operative findings and results of surgical treatment of penile fracture (PF) in men who have sex with men(MSM) with emphasis on sexual complications.Materials and Methods:We studied 216 patients underwent surgical correction of PF at our hospital. Patients self-identified as MSM were followed for at least 6 months. Demographic data, presentation, operative findings, International Index of Erection Function - 5 (IIEF-5) and the Premature Ejaculation Diagnostic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Barros et al reported premature ejaculation and delayed ejaculation cases after penile fracture in their study [10]. However, data on sexual function after an injury is limited.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Barros et al reported premature ejaculation and delayed ejaculation cases after penile fracture in their study [10]. However, data on sexual function after an injury is limited.…”
Section: Discussionmentioning
confidence: 88%
“…Complications such as erectile dysfunction, penile deviation, priapism, urethrocavernosal fistula, and urethral stricture may occur despite immediate surgical intervention [9]. Ejaculatory problems were reported after penile fracture in a recent study [10]. Ejaculatory dysfunction may be related to the penile injury or post-traumatic emotional conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Etiology can vary due to many factors, such as geographic region, sociocultural characteristics, marital status and masturbation habits. Heterosexual vaginal intercourse is reported as the main cause of PF in the World, and there have been reports of occurrence during homossexual anal coitus (7). In Mediterranean and Middle Eastern countries, the majority of cases result from self-inflicted penile manipulation during erection to achieve detumescence (8).…”
Section: Discussionmentioning
confidence: 99%
“…RGU is recommended when abnormalities are found in the IPSS questionnaire or uroflowmetry to identify possible urethral stricture or other complications. (8,(22)(23)(24). Short penile urethral stenosis can be treated with sequential dilatations (4,21).…”
Section: Discussionmentioning
confidence: 99%